Elfriede Jelinek and the beauty of princesses through the mirror - Ripoll León, Verónica (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2017)
Elfriede Jelinek, winner of the Literature Nobel Prize in 2004, is a tireless creator of stereotyped characters. Through the application of irony, the protagonists of her works are used with the intention of exciting critical thought about the social roles and actions expected to be played by women and men within a society. A year before being awarded the Nobel Prize, Jelinek released a body of plays under the title of Death and the Maiden I-V. Princess Plays (Der Tod und das Mädchen I-V. Prinzessinendramen, 2003). In this work, the Austrian writer rewrote two of the most famous fairytales featuring princesses, such as Snow White and Sleeping Beauty, as well as a legend played by Rosamunde. These tales are part of the core of Western literary tradition. In using them, she reinvents the story of other real characters and women from our historic and cultural panorama: Jacqueline Kennedy Onassis or writers like Sylvia Plath and Ingeborg Bachmann. The main goal of the present paper is to analyse the problem posed by the existence of a beauty canon in these Princess Plays insofar as the construction and depiction of female identity is subdued by the control and supremacy of a patriarchal society. To do so, and following a psychoanalytical approach, the theme of the mirror will be the main focus as an instrument which brings or hinders the acknowledgement of these princesses.